2017
DOI: 10.1063/1.4976978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic simulations of N2-broadened methane line shapes and comparison with experiments

Abstract: Absorption spectra of methane transitions broadened by nitrogen have been calculated for the first time using classical molecular dynamic simulations. For that, the time evolution of the auto-correlation function of the dipole moment vector, assumed along a C–H axis, was computed using an accurate site-site intermolecular potential for CH4–N2. Quaternion coordinates were used to treat the rotation of the molecules. A requantization procedure was applied to the classical rotation and spectra were then derived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…As demonstrated previously for O2 [18,24] and for other molecular systems [15,17,19,20,30], the non-Voigt effects observed on the rCMDS-calculated spectra are in very good agreement with those of measured spectra (through comparison of their Voigt fits residuals and parameters). However, line broadening coefficients predicted by rCMDS can be significantly different from measured values.…”
Section: Analysis Proceduressupporting
confidence: 85%
See 1 more Smart Citation
“…As demonstrated previously for O2 [18,24] and for other molecular systems [15,17,19,20,30], the non-Voigt effects observed on the rCMDS-calculated spectra are in very good agreement with those of measured spectra (through comparison of their Voigt fits residuals and parameters). However, line broadening coefficients predicted by rCMDS can be significantly different from measured values.…”
Section: Analysis Proceduressupporting
confidence: 85%
“…It was shown that the non-Voigt effects observed in the measured spectra are well predicted by these first-principles calculations, for various molecular systems (e.g. [17][18][19][20][21][22]) although the difference between the computed and measured line widths could be several percent. In [15,16], the calculations were thus empirically improved by introducing a measured value of the line width into the computed auto-correlation function of the transition dipole moment, where the line-shape equals the Fourier-Laplace transform of the latter quantity.…”
Section: Introductionmentioning
confidence: 71%
“…In this manner, CMDS were used to predict the absorption in the far wing of the 3 band of CO2 26,31 , absorptions induced by collisions in the far infrared for pure CO2 32 , pure N2 33 as well as for N2 and CO2 in collision with H2O 34 . Furthermore, when an appropriate requantization procedure 35 is used, CMDS can even predict the shapes of isolated transitions 29,[35][36][37][38][39] . Indeed, fits of measured spectra and rCMDS-calculated ones with the Voigt profile showed that the obtained collisional (Lorentz) line widths are in good agreement and that the Voigt-fit residuals are also very consistent 29,[35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when an appropriate requantization procedure 35 is used, CMDS can even predict the shapes of isolated transitions 29,[35][36][37][38][39] . Indeed, fits of measured spectra and rCMDS-calculated ones with the Voigt profile showed that the obtained collisional (Lorentz) line widths are in good agreement and that the Voigt-fit residuals are also very consistent 29,[35][36][37][38][39] . In this work, a more advanced step in the use of rCMDS to study spectral line shapes is made by directly predicting the HT profile parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As first demonstrated for pure CO 2 [117,118] and confirmed for other systems [119,120], these requantized CMDS (rCMDS) closely predict the observed relative deviations of line shapes from the VP without adjusting parameters. Note that an alternative requantization was proposed in [121], which is more suitable for light rotors and was successfully applied to HCl [121] and CH 4 [122] lines. It also enables one to constrain the positions and intensities of the lines in the calculated spectrum to literature values (taken from a database, for instance), a possibility that was used in [123,124].…”
Section: Direct and Empirically Corrected Predictions From Molecular mentioning
confidence: 99%